2019
DOI: 10.1177/1359104519827629
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and psychiatric comorbidity of adolescent-onset anorexia nervosa

Abstract: Objective: To assess the outcome of adolescents with anorexia nervosa (AN) about 20 years after first treatment. Methods: Sixty-two women diagnosed with AN during adolescence were invited to participate. Of these 62 patients, 38 agreed to participate and were assessed with a battery of questionnaires and interviews. A control group of 30 women of similar age was also assessed. Results: Of the patients who completed the full assessment, 13 (34%) presented some degree of eating disorder (ED) at follow-up (10 (26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…The efficacy of “step down” care in preventing relapse may merit further research. The more favorable prognosis associated with shorter duration of illness [ 14 , 18 , 20 , 34 , 35 , 39 , 41 , 66 ] suggests that early intervention may be important, as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of “step down” care in preventing relapse may merit further research. The more favorable prognosis associated with shorter duration of illness [ 14 , 18 , 20 , 34 , 35 , 39 , 41 , 66 ] suggests that early intervention may be important, as well.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of psychological factors such as depression, anxiety, harm avoidance, eating disorder psychopathology, and motivation for recovery have been mixed [ 12 , 13 , 33 38 ]. Though multiple longitudinal studies have examined the course of AN, the majority of studies focus on predictors and correlates of outcomes such as diagnostic status, mortality, and rates of relapse [ 5 , 7 , 10 12 , 15 , 16 , 31 , 33 36 , 39 41 ]. Prior studies on inpatient samples specifically have tended toward examining predictors of outcome unrelated to treatment (e.g., age of onset, comorbidities, family support) and report overall prognosis categorically [ 42 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…All studies reported DUED using a statistic of central tendency. Four studies (n = 2,246) reported a component breakdown of DUED, (Beat, 2017;Brown et al, 2018;Gumz et al, 2018;Schlegl et al, 2019), two (n = 787) reported DUED and its crosssectional association with symptom severity (Bühren et al, 2013;Flynn et al, 2020), and one (n = 38) reported associations between DUED and long-term clinical outcomes (Andrés-Pepiñá et al, 2019). Three studies (n = 721) attempted to experimentally manipulate DUED (Brown et al, 2018;Flynn et al, 2020;Gumz et al, 2018), one of which (n = 142) also reported the prospective associations between DUED and clinical outcomes (McClelland et al, 2018).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A series of publications on very long-term (10–20 years) follow-up studies of inpatients with an eating disorder showed that, respectively 64% of persons previously diagnosed with anorexia nervosa, 53% of those previously diagnosed with bulimia nervosa, and 30% of those previously diagnosed with BED, still met diagnostic criteria for an eating disorder at follow-up; a further 6% for anorexia nervosa, 9% for bulimia nervosa and 31% for BED had remaining eating disorder symptoms [ 7 , 8 ▪▪ , 9 ]. Higher recovery rates of anorexia nervosa were reported in two smaller long-term (≥20 years) follow-up studies of adolescent-onset anorexia nervosa; one on an outpatient sample [ 10 ], the other on a community sample [ 11 ▪▪ ]. In both studies, around 65% of the cases were in complete remission at follow-up.…”
Section: Introductionmentioning
confidence: 99%